2015
DOI: 10.1158/1078-0432.ccr-14-2862
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Nonenhancing Tumor Burden in Gliomas Using Effective T2 Maps Derived from Dual-Echo Turbo Spin-Echo MRI

Abstract: Purpose Evaluation of nonenhancing tumor (NET) burden is an important, yet challenging part of brain tumor response assessment. The current study focuses on using dual echo turbo spin echo MRI as a means of quickly estimating tissue T2, which can be used to objectively define NET burden. Experimental Design A series of experiments were performed to establish the use of T2 maps for defining NET burden. First, variation in T2 was determined using ACR water phantoms in 16 scanners evaluated over 3 years. Next, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…Recently, there has been renewed interest in evaluating role of relaxometry in the assessment of non-enhancing tumor burden and response to anti-angiogenic drug therapy 5255 . Although most of these recent studies focus on role of T 2 relaxometry, a recent study has demonstrated that T 1 mapping may play a significant role in earlier detection of recurrent tumor in patients on anti-angiogenic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been renewed interest in evaluating role of relaxometry in the assessment of non-enhancing tumor burden and response to anti-angiogenic drug therapy 5255 . Although most of these recent studies focus on role of T 2 relaxometry, a recent study has demonstrated that T 1 mapping may play a significant role in earlier detection of recurrent tumor in patients on anti-angiogenic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The total scan time for CEST‐EPI was approximately 5 min. Since many of the low‐grade gliomas and anaplastic tumors contained significant non‐enhancing disease, values of MTR asym within T 2 ‐hyperintense lesions representative of non‐enhancing tumor were evaluated for these patients and compared across tumor grade.…”
Section: Methodsmentioning
confidence: 99%
“…In our study we applied histogram matching to facilitate comparison of MR images between patients. In a multi-institutional setting, more sophisticated preprocessing techniques may be used to minimize the effects of different imaging acquisition protocols (38). …”
Section: Discussionmentioning
confidence: 99%